Choosing Esteem - Hanasz, Waldemar (Sensus Historiae, 2021)
Esteem can be seen among basic goods every individual seeks in life, yet its philosophical status has not been satisfactorily explored. There is, in particular, a problem vital to the notion’s practical viability: whether esteem can be a matter of deliberate choice. This study argues that despite some problems exposed by critical studies on cognitive phenomena, esteem - as a complex cognitive, emotional, and social notion - is not beyond our intentional and rational control. In fact, it is founded on numerous choices and decisions to be made, especially while choosing the criteria of our judgments and deciding how to interact with people we might possibly build, give, and gain esteem. Importantly, esteem has to be viewed as a continuous cognitive process, hence we can even recognize some systematic ways of educating and cultivating it. It is a promising conclusion, suggesting that some positive forms of interpersonal relations - esteem and trust among them - can be generated and developed among people.